Injection moulding of hap-zirconia composite using palm stearin binder system: article - Muhammad Faizi Ibrahim, Muhammad Faizi Ibrahim; Istikamah Subuki,, Istikamah Subuki, (2019)
The main objective of this paper is to analyze the ability of the feedstock HAp-ZrO2 which has different composition with Palm Stearin (PS) based binder system. In this research, the feedstock was classified by different weight percentage composition which 90-10, 80-20 and 70-30 of the HAp-ZrO2 with the same ratio 60% of their optimum powder loading to palm stearin. Thus, the performance of HAp-ZrO2 composite powder is studied through the Thermogravimetric Analysis (TGA) which showing that palm stearin binder system completely being removed in the present of high temperature 5000C with heating rate of 10°C/min.While the analysis of Scanning Microscopy Electron (SEM) to identify their physical characterization of feedstock. The effect of Zirconia content in the composition can be investigated through rheological test using Rosand RH2000 capillary rheometer. During the rheological test, the feedstock containing the mixture and the binder carried out pseudoplastic behavior and viscosity. The binder in the feedstock gives exceptional properties to ensure the success of injection molding process.